Sparse evidence for equine or avian influenza virus infections among Mongolian adults with animal exposures. Issue 6 (13th August 2013) - Khurelbaatar, Nyamdavaa; Krueger, Whitney S.; Heil, Gary L.; Darmaa, Badarchiin; Ulziimaa, Daramragchaa; Tserennorov, Damdindorj; Baterdene, Ariungerel; Anderson, Benjamin D.; Gray, Gregory C.
<x xml:space="preserve">Abstract</x> In recent years, Mongolia has experienced recurrent epizootics of equine influenza virus (EIV) among its 2·1 million horses and multiple incursions of highly pathogenic avian influenza (HPAI) virus via migrating birds. No human EIV or HPAI infections have been reported. In 2009, 439 adults in Mongolia were enrolled in a population‐based study of zoonotic influenza transmission. Enrollment sera were examined for serological evidence of infection with nine avian, three human, and one equine influenza virus strains. Seroreactivity was sparse among participants suggesting little human risk of zoonotic influenza infection.